PPM DECISION SUPPORT AND RISK MANAGEMENT PADA SOWAN COFFE SHOP KOTA SURABAYA - Aldea Mita Cheryta; Rudiatno Rudiatno; Chandra Kartika (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2022)
Abstract Normative community service is stated by several empirical problems obtained from the results of initial indept interviews with business partners, so that later in the community empowerment program solutions can be formulated to overcome the problems faced by partners. This community service was carried out at one of the partners of Sowan Coffe Shop Surabaya which is located in the Taman Apsari area of Surabaya. The problems faced are 1) Lack of product consistency; 2) Often the product is unavailable or out of stock; 3) Some places cannot be used when huan; 4) Rarely do promotions; 5) There is no classification of company risk management in product development; 6) The calculation of profit/loss is still not complete; 7) Strategies to accelerate the break event point have not been achieved optimally. This is a challenge for researchers considering the strategic location but has a lot of coffe shop competitors. Increasing the production and quality of coffee servings is one of the most important things. This community service is specifically carried out through indept interviews, mentors, and training consistently. The results of community development are oriented towards 1) product consistency 2) product stock reserves; 3) development of partner locations; 4) marketing promotion strategies; 5) classifying risk management; 6) automatic calculation of profit and loss; 7) acceleration of the break event point. Keywords: Decision Support; Risk Management